5-HT Drives Mortality in Sepsis Induced by Cecal Ligation and Puncture in Mice. (13th June 2017) - Zhang, Jingyao; Bi, Jianbin; Liu, Sushun; Pang, Qing; Zhang, Ruiyao; Wang, Shun; Liu, Chang
Abstract : Sepsis is defined as a life-threatening organ dysfunction caused by a dysregulated host response to infection with a high mortality. 5-Hydroxytryptamine (5-HT) is an important regulatory factor in inflammation. The aim of this study is to investigate the role of 5-HT on cecal ligation and puncture- (CLP-) induced sepsis in the mouse model. CLP was performed on C57B/6 wild-type (WT) mice and tryptophan hydroxylase 1 ( TPH1 ) knockout (KO) mice. The results showed that the 5-HT-sufficient group mice had a significantly lower survival rate than the 5-HT-deficient group in CLP-induced sepsis and septic shock. The KO-CLP sepsis group received a lower clinical score than the WT-CLP sepsis group. Meanwhile, the body temperature of mice in the KO-CLP sepsis group was higher than that in the WT-CLP sepsis group and was much closer to the normal body temperature 24 hours after CLP. The tissue histopathology analysis revealed that 5-HT markedly exacerbated histological damages in the peritoneum, lung, liver, kidney, intestinal tissue, and heart in sepsis. Moreover, significant lower levels of TNF- α, IL-6, bacterial loads, MPO, and ROS were discovered in the KO-CLP sepsis group in contrast to the WT-CLP sepsis group. In conclusion, 5-HT drives mortality and exacerbates organ dysfunction by promoting serum cytokines and bacterial loads as well as facilitating oxidative stress in the process of sepsis.